The Influence of Financial Literacy and Lifestyle on The Decision to Purchase Boarding Room Services for Students of the University of Tribhuwana Tunggadewi Malang - Dafrosa Ngola; Nur Ida Iriani; Warter Agustim (International Journal of Management and Business, 2025)
Financial literacy and lifestyle are several important factors in determining purchasing decisions. This research aims to partially and simultaneously determine the influence of financial literacy and lifestyle on purchasing decisions for boarding room services among the Unitri management student class of 2021. The research was carried out using quantitative methods. Determination of the sample using probability sampling. The data collection technique used by researchers is a questionnaire. The data analysis method used is multiple linear regression using the SPSS program. The research results prove that financial literacy partially influences the decision to purchase a boarding room with a calculated t value of 12.423 and a t table of 1.994 and lifestyle also influences the decision to purchase a boarding room with a calculated t value of 5.245 and a t table of 1.994. Financial literacy and lifestyle simultaneously influence the decision to purchase a boarding room with an Fcount value of 98.721 and an Ftable of 3.13. This research can provide recommendations for boarding service providers regarding important aspects that need to be considered in attracting student attention